Physical fitness as a factor influencing the physical attractiveness of young women - Lic, Łukasz; Lipecki, Krzysztof; Kukla, Paweł (Health Promotion & Physical Activity, 2024)
Aim of the study: The aim of the study was to identify body build characteristics and components of physical fitness that have the greatest effect on subjective self-assessment and external judgment of the physical attractiveness of young women. Materials and methods: The participants were 129 female students of tourism and recreation from Kraków aged 19 to 26 years. The level of physical fitness of the participants was evaluated using the European Physical Fitness Test. Physical attractiveness was assessed by the participants themselves and by external judges. The body height, body weight, and waist and hip circumferences of the women were measured. Furthermore, body water and body fat percentages were estimated. Results: The analysis of the correlation between attractiveness and physical fitness indicates that in all the cases examined, those who performed better in the fitness tests not only feel but are also assessed as more attractive. Not all correlations proved to be statistically significant. However, the results obtained indicate a positive relationship between physical fitness and attractiveness of young women. The results of the research indicate that the parameters related to fat (absolute hip circumference, BMI index, and body fat percentage) have the greatest effect on the physical attractiveness of body build in both subjective and external judgments of young women. Conclusions: The young women studied with higher physical fitness and lower values of fat-related parameters were assessed and perceived as more physically attractive. Physical fitness had a greater impact on the subjective than external judgment of physical attractiveness. The above finding can be a factor motivating to improve physical fitness and to undertake sporting activities.